DESAIN WEB SEBAGAI MEDIA PROMOSI DAN INFORMASI PADA RAFI STAMP SEMARANG - Eni Dwifitri Astutiningtias; Danang Danang (Pixel :Jurnal Ilmiah Komputer Grafis, 2018)
Sales and marketing systems of goods and services via the internet are also in great demand by businesses. By providing a place as a medium for communicating and transacting cyberspace is able to reach the corners of the world making it possible for business communication via the internet. No wonder so many businesses put up websites on the internet to sell or just to display their work. With an attractive website appearance can also be a special attraction to invite consumers to visit the website. One of the uses of the website is to make it easy to exchange, update information and do business through internet users. A website can be the work of individuals or individuals, or show ownership of an organization, company, and usually the website shows some special topics, or certain interests. In this case as offered by Rafi Stamp Semarang, namely Graphic Design Services and Computer Sales. The most important part of a website is the design, the design of the face of an attractive website will encourage visitors to see more deeply the contents of the website and can interact in business and others. Therefore, the author takes the title "Web design as a promotional media and information on Semarang Rafi Stamp As a Media Promotion"In designing the website the author uses Adobe Photoshop CS software for the initial design, Swish Max for animation and DreamweaverMX for HTML design.